Morphological and Histological Structures of Gonad of Coconut Crab (Birgus latro) - Suzana Refiani; Sulistiono , (Jurnal Ilmu-Ilmu Perairan dan Perikanan Indonesia, 2009)
The study was aimed to investigate the secondary morphological and histological structures of gonad of coconut crab (Birgus latro). Morphologically, male and female gonads were described based on size, surface condition, colour and ocupied stage in abdomen. Histologically, male gonad was described based on appearance of spermatocyte, spematid and spermatophore using PAS-Hematoksilin method, while female gonad was described on oocyte development, nucleus condition, and deposit of oocyte using Hematoksilin-Eosin methods. Morphologically, testes are smooths, white-brownish, and occupied about 9-40% abdoment, while ovarium surface are smooth-granule, whitish, grey-dark, red, and occupied about 25-80% abdoment. Histologically, the testes showed spermatocyte, spermatid, and spermatozoa in spermatophore, while the ovarium showed oocyte at premature-mature conditions.Key words: Morphological and histological structures, gonad, coconut crab (Birgus latro).